In ovo Administration of Defined Lactic Acid Bacteria Previously Isolated From Adult Hens Induced Variations in the Cecae Microbiota Structure and Enterobacteriaceae Colonization on a Virulent Escherichia coli Horizontal Infection Model in Broiler Chickens - Arreguin-Nava, Margarita A.; Graham, Brittany D.; Adhikari, Bishnu; Agnello, Melissa; Selby, Callie M.; Hernandez-Velasco, Xochitl; Vuong, Christine N.; Solis-Cruz, Bruno; Hernandez-Patlan, Daniel; Latorre, Juan D.; Tellez, Guillermo; Hargis, Billy M.; et al. (Frontiers in Veterinary Science, 2020)
The effects of in ovo administration of a defined lactic acid microbiota (LAM), previously isolated from adult hens, in the cecae microbiota structure and Enterobacteriaceae colonization after exposure to virulent Escherichia coli during the hatching phase of broiler chickens was evaluated. Embryos inoculated with LAM showed a significant (P < 0.05) reduction of Enterobacteriaceae colonization at day-of-hatch (DOH) and d7. Furthermore, there was a significant increase in total lactic acid bacteria (LAB) on DOH, BW DOH, BW d7, d0-d7 BW gain, and reduced mortality d0-d7 was observed in the LAM group compared to PBS control. The bacterial composition at the family level revealed that the Enterobacteriaceae was numerically reduced, while the Ruminococcaceae was significantly increased in the LAM group when compared to the PBS control. Moreover, the bacterial genera Proteus, Butyricicoccus, and unidentified bacterial genera of family Lachnospiraceae and Erysipelotrichaceae were significantly enriched in the LAM group. In contrast, the Clostridium of the family Peptostreptococcaceae and unidentified genus of family Enterobacteriaceae were significantly abundant in the PBS Control group. In summary, in ovo administration of a defined lactic acid microbiota isolated from adult hens did not affect hatchability, improved BWG and reduced mortality at d7, induced variations in the cecae microbiota structure and reduced Enterobacteriaceae colonization on a virulent E. coli horizontal infection model in broiler chickens.